Strengthening and promotion of the Revista Peruana de Ciencias de la Salud during the COVID-19 pandemic - Yance-Yupari, Victoria (2022)
The Revista Peruana de Ciencias de la Salud (RPCS) is edited and published by the Universidad de Huánuco through its Editorial Office and in collaboration with the national and international members of the editorial and scientific committee (1). During its history, the journal has been characterized by its constant dedication to strengthen and promote its visibility in the academic and scientific environment. The purpose of this editorial is to present a summary of the actions carried out in this context and the expected effects and impacts.